Peculiarities of legal regulation of activities of the National Police of Ukraine in the field of ensuring information security in Ukraine (Law and Safety, 2020)
Based on the analysis of scientific concepts and legal principles the author has provided the definition of information security, provision of information security in Ukraine and has characterized its components. The current state of legal regulation of the organization and activity of cyberpolice units of the National Police of Ukraine has been analyzed. Particular attention has been paid to the legal analysis of the tasks, functions and structure of the Cyberpolice Department of the National Police of Ukraine. Special attention has been drawn to certain shortcomings of Ukrainian legislation in the field of ensuring information security by the police, its compliance with the norms and standards of international law. Taking into account the specifics of the tasks, the author has provided characteristics of the functions of cyberpolice units in the information sphere, which should be divided according to the purpose into: 1) basic (external), which are focused on law enforcement and preventive aspects; 2) auxiliary (intrasystem), which are focused on promoting the implementation of basic functions, the introduction of appropriate management mechanisms within the system.It has been stated that the modern system of ensuring information security and cybersecurity in Ukraine should be one effective system, consisting of such mandatory components as legal, educational and technical. It has been concluded that in order to improve the legal principles for the organization and activities of cyberpolice units of the National Police in the field of ensuring information security and counteracting cyber threats, first of all, it is necessary to optimize the organizational structure of cyberpolice, reasonably distribute the functions (powers) between cyberpolice units and other subjects combating cyber threats in Ukraine, to create appropriate conditions for reaching a qualitatively new level of interaction between them and coordination of their activities in the field of ensuring information security in modern conditions.
Keywords: information security; legal regulation; National Police of Ukraine; cyber police units; counteraction; information sphere